The influence of medical insurance on the use of basic public health services for the floating population: the mediating effect of social integration - Yulin Li; Dongmei Dou (BMC, 2022)
Abstract Background The accessibility and fairness of the floating population's access to basic public health services have an important impact on improving the health level of the whole population. Existing studies have shown that medical insurance and social integration have an impact on basic public health services, but there are few studies on the specific influence path between the three. Therefore, the research purpose of this paper is to explore the effects of medical insurance for urban and rural residents and basic medical insurance for urban employees on the utilization of basic public health services, and to analyze the mediating effect of social integration. Methods The data in this paper are derived from the 2017 China Mobile Population Dynamic Monitoring Survey data, which collects information on 31 provinces (regions, cities) and Xinjiang Production and Construction Corps mobile population 169,989 people, all of whom come from China's relatively concentrated mobile population inflow areas (NHC FPSCo. 2021. Floating Population Service Center of NHC). After deleting part of the missing data and replacing the mean value, 154,586 people were finally included in the analysis. The proportion is 90.9%. Based on the data of China's floating population dynamic survey in 2017,we used Logistic regression method to analyze the effects of basic medical insurance for urban and rural residents, basic medical insurance for urban employees and social integration on the utilization of basic public health services. Then we used the Bootstrap method of structural equation model to analyze the mediating effect of social integration. Results Medical insurance for urban and rural residents (β = 0.236;95%CI:1.195 ~ 1.342) has positive impact on health education, it (β = 0,190;95%CI:1.150 ~ 1.272) also has positive impact on the establishment of residents' health records. Social integration (including political participation (β = 0.312;95%CI:1.324 ~ 1.410),activity participation (β = 0.724;95%CI:2.009 ~ 2.119), identity (β = 0.421; 95%CI:1.387 ~ 1.675))has positive impact on health education, it ((β = 0.312;95%CI:1.324 ~ 1.410), (β = 0.404;95%CI:1.463 ~ 1.534), (β = 0.282;95%CI:1.191 ~ 1.477)) also has positive impact on the establishment of residents' health records. In addition, BMIUE (β = 0.169;95%CI:1.150 ~ 1.219) has an impact on the establishment of residents' health records. The direct effect of medical insurance on the utilization of public health services was 0.092 (95%CI: 0.093 ~ 0.103), social integration was a partial mediator, the mediating effect was 0.127 (95%CI: 0.108 ~ 0.127), and the mediating effect size was 57.73%. Conclusions Medical insurance can directly promote the floating population to use basic public health services, and can indirectly promote the improvement of public health service utilization level through social integration.